Frank Povah and Chris Cruise performing and being interviewed by Rob Willis in the Rob and Olya Willis folklore collection. - Povah, Frank, 1940-2020.; Cruise, Christopher, 1945-; Willis, Rob, 1944-; Willis, Olya. (2015)
Folkloric recording.
Recorded with Olya Willis.
Recorded on 31 March and 1-2 April 2015 at the National Library of Australia, Canberra, Australian Capital Territory.
Digital master available
Summary not yet available.
Keywords: Povah, Frank, -- 1940-2020 -- Interviews; Cruise, Christopher, -- 1945- -- Interviews; Folk musicians -- Australia -- Interviews; Folk musicians